Fournier's Gangrene and Septic Cardiomyopathy in the Context of a Clinical Case: An Underestimated Diagnosis - Ortega Martinez, Rommer Alex (2024)
Fournier's gangrene, frst described in 1883, is a necrotizing infection that occurs in the perineal and abdominal areas. It develops in patients with risk factors such as diabetes mellitus, obesity, alcoholism, hypertension, atherosclerosis, and immunosuppression. Its etiology is a polymicrobial synergy of gram-positive, gram-negative, and other pathogens, which require the presence of an initial lesion in the genital or perineal region and are responsible for tissue destruction, endarteritis, and microthrombosis. Systemically, they cause multiorgan failure, such as myocardial dysfunction induced by sepsis or septic cardiomyopathy, frst described in 1984, which can manifest as systolic or diastolic dysfunction of both ventricles, presence of cardiac arrhythmias, preceded by QT interval prolongation, and elevated cardiac troponins. This is similar to the presentation of our 71-year-old patient who had a favorable outcome.